2015
DOI: 10.1115/1.4030334
|View full text |Cite
|
Sign up to set email alerts
|

Forming of Al 5182-O in a Servo Press at Room and Elevated Temperatures

Abstract: Aluminum alloys are increasingly used in automotive manufacturing to save weight. The drawability of Al 5182-O has been proven at room temperature (RT) and it is also shown that formability is further enhanced at elevated temperatures (ETs) in the range of 250–350 °C. A cost effective application of ET forming of Al alloys can be achieved using heated blank and cold dies (HB–CD). In this study, the material behavior of Al 5182-O is characterized using tensile test and viscous bulge test at RT. The nonisotherma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 11 publications
(16 reference statements)
1
7
0
Order By: Relevance
“…Their research showed that the formability of aluminum alloy was improved with the increase in forming rate, and the relation between slide speed and PSC indicated an acceleration effect existed on the formability. Similar research has been carried out on Al 5182-O by Ju et al [15]; the results showed that better part quality could be achieved with a higher forming speed, which could be considered as a more efficient process in production. Mori et al [16] performed cold stamping and hot stamping with different stamping speed on ultra-high-strength steel.…”
Section: Introductionsupporting
confidence: 57%
“…Their research showed that the formability of aluminum alloy was improved with the increase in forming rate, and the relation between slide speed and PSC indicated an acceleration effect existed on the formability. Similar research has been carried out on Al 5182-O by Ju et al [15]; the results showed that better part quality could be achieved with a higher forming speed, which could be considered as a more efficient process in production. Mori et al [16] performed cold stamping and hot stamping with different stamping speed on ultra-high-strength steel.…”
Section: Introductionsupporting
confidence: 57%
“…Laurent et al 22 reported that formability improves above die temperatures of 150°C for Al5754. Some of the recently published works also deal with the warm forming research on aluminum alloys [23][24][25][26][27][28] and steels [29][30][31][32][33] with a focus on specific applications. It seems from the literatures that the technology of warm forming is limited to laboratory research only.…”
Section: Introductionmentioning
confidence: 99%
“…So, the properties of low-carbon steel were used from literature; (b) the heat transfer coefficient which determines the amount of the heat transferred from sheet to the dies was considered as a constant value. However, as determined experimentally, this value is a function of the gap and pressure between the sheet and the die [9,11]; (c) the sheet and the tools are simulated as surface elements and thermal integration points through the thickness were considered to analyze the heat conduction inside the tools; (d) a constant value of the COF is considered in all simulations and it is known that the COF is not constant in all locations in the die during stamping. Figure 3 shows the predicted maximum temperature generated at the die/sheet interface compared to the experimental results.…”
Section: Tools Sheetmentioning
confidence: 99%
“…Therefore, it is important to accurately determine the fraction of deformation work which goes to increasing the temperature of the material during the sheet forming process. There are a few studies that investigated the temperature generation in forming of AHSS and aluminum alloys using numerical or experimental procedures [3,4,8,9]. Kim et al [3], investigated the shear fracture at die corner radius in draw bending test of DP980 and they concluded that the deformation-induced heating, in the order of 75 C, has a dominant effect on the occurrence of shear failure [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation